SOCIAL UPLIFTMENT OF COLACHEL FISHERFOLKS - L. Amala Mary; N. Subha Nanthini (ShodhKosh: Journal of Visual and Performing Arts, 2024)
The Colachel fishing community in India faces financial struggles due to limited savings and borrowing. The community faces various demographic challenges, including gender, age, marital status, and family structure. To address these issues, government should enhance fish preservation, expand export markets, improve infrastructure, educate the community, and provide financial assistance.